Can consumers learn to ask three questions to improve shared decision making? A feasibility study of the ASK (AskShareKnow) Patient–Clinician Communication Model® intervention in a primary health‐care setting. (14th September 2015) - Shepherd, Heather L; Barratt, Alexandra; Jones, Anna; Bateson, Deborah; Carey, Karen; Trevena, Lyndal J; McGeechan, Kevin; Del Mar, Chris B; Butow, Phyllis N; Epstein, Ronald M; Entwistle, Vikki; Weisberg, Edith
Abstract: Objective: To test the feasibility and assess the uptake and acceptability of implementing a consumer questions programme, AskShareKnow, to encourage consumers to use the questions '1. What are my options; 2. What are the possible benefits and harms of those options; 3. How likely are each of those benefits and harms to happen to me?' These three questions have previously shown important effects in improving the quality of information provided during consultations and in facilitating patient involvement. Methods: This single‐arm intervention study invited participants attending a reproductive and sexual health‐care clinic to view a 4‐min video‐clip in the waiting room. Participants completed three questionnaires: (T1) prior to viewing the intervention; (T2) immediately after their consultation; and (T3) two weeks later. Results: A total of 121 (78%) participants viewed the video‐clip before their consultation. Eighty‐four (69%) participants asked one or more questions, and 35 (29%) participants asked all three questions. For those making a decision, 55 (87%) participants asked one or more questions, while 27 (43%) participants asked all three questions. Eighty‐seven (72%) participants recommended the questions. After two weeks, 47 (49%) of the participants recalled the questions. Conclusions: Enabling patients to view a short video‐clip before an appointment to improve information and involvement in health‐care consultations is feasible and led to a high uptake of question asking in consultations. Practice Implications: This AskShareKnow programme is a simple and feasible method of training patients to use a brief consumer‐targeted intervention that has previously shown important effects in improving the quality of information provided during consultations and in facilitating patient involvement and use of evidence‐based questions.